THE EFFECT OF JOB STRESS AND FLEXIBLE WORK ARRANGEMENT (FWA) ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE FOR EMPLOYEES OF PT FEDERAL INTERNATIONAL FINANCE GROBOGAN REGENCY - Putri Suhita Wardani; Fariha azzahra (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2024)
Background: In an era of increasingly fierce business competition, service industry companies face challenges that demand change and innovation. In today's highly competitive conditions, companies are required to improve human resource performance through low levels of work stress and implementing flexible work arrangements (FWA). Apart from that, there are other factors that support performance, namely job satisfaction.Purpose: : Based on the background and problem formulation that has been explained, the aim of this research is to analyze and describe the effect of work stress on job satisfaction, analyze and describe the effect of flexible work arrangements (FWA) on job satisfaction, analyze and describe the effect of work stress on performance employees, analyze and describe the effect of flexible work arrangements (FWA) on employee performance, analyze and describe the effect of job satisfaction on employee performance, analyze and describe the effect of work stress on employee performance with job satisfaction as an intervening variable, analyze and describe the effect of flexible work arrangements ( FWA) on employee performance with job satisfaction as an intervening variable.Method: This research uses a quantitative approach which aims to test the hypothesis formulated. Determining the number of samples used the Slovin formula with purposive sampling technique and obtained a sample of 84 respondents. Analyzed using the Partial Least Square (PLS) statistical analysis technique version 4.0.Conclusion: So, work stress, flexible work arrangements (FWA), and job satisfaction as intervening variables play a role in improving employee performance.Suggestion: In this research, work stress on job satisfaction (H1), work stress on employee performance (H3), and flexible work arrangement (FWA) (H4) have a weak relationship with employee performance. Therefore, it is recommended that the future agenda be to develop variable measurements in order to provide better results.